Potencialidades e desafios no ensino de geografia: estudo de caso da metodologia do projeto 'Nós Propomos!' no Colégio Estadual Mário de Andrade, Francisco Beltrão – Pr - Macedo, Eduardo Sebastião (2024)
Through the analysis encouraged in the preparation of the case study, this work aims to understand how the adoption of the “We Propose!” project contributes to the provision of geographic education among 7th year students at Mário de Andrade Public School, in Francisco Beltrão – Paraná. The investigation was undertaken by conducting a bibliographical review, as well as by carrying out activities aligned with the methodology of the "We Propose!" project, which began in 2022 with 7th year students at Mário de Andrade School, located in Francisco Beltrão, Paraná. These practices were continued through an after-school teaching project, involving the same group of students in the subsequent academic year. Thus, the study was conducted with a total of 34 participants throughout the years 2022 and 2023, during the period in which they were enrolled in the 7th and 8th years of Elementary School. It was verified, through the study carried out, that the adoption of the methodological steps proposed by the “We Propose!” facilitated the approximation between knowledge and students, and that the activities carried out within the scope of Geography teaching, in this context, became a responsibility of collective construction and not an imposition. A characteristic that converges with the concepts of geographic education and territorial citizenship, which underlie the research.